A convergent mechanism of sex determination in dioecious plants: Distinct sex-determining genes display converged regulation on floral B-class genes - Zhang, Xianzhi; Pan, Linsi; Guo, Wei; Li, Yongquan; Wang, Wencai (Frontiers in Plant Science, 2022)
Sex determination in dioecious plants has been broadly and progressively studied with the blooming of genome sequencing and editing techniques. This provides us with a great opportunity to explore the evolution and genetic mechanisms underlining the sex-determining system in dioecious plants. In this study, comprehensively reviewing advances in sex-chromosomes, sex-determining genes, and floral MADS-box genes in dioecious plants, we proposed a convergent model that governs plant dioecy across divergent species using a cascade regulation pathway connecting sex-determining genes and MADS-box genes e.g., B-class genes. We believe that this convergent mechanism of sex determination in dioecious plants will shed light on our understanding of gene regulation and evolution of plant dioecy. Perspectives concerning the evolutionary pathway of plant dioecy are also suggested.